Terapia de grupo como facilitadora da adesão do paciente com disfonia comportamental - Fahning, Ana Karina Cascudo Alves (2015)
Engagement and continuity in voice treatment is still a field to bewidely discussed because the frequent abandonment and resistance to change behavior are impediments to occur success in voice therapy. It has been the assumption that group therapy provides an opportunity to individual exchange of experiences and the sharing of their anguish and frustrations. Given this, it is proposed to check the stage of readiness voice therapy to pre and post group therapy in patients with behavioral dysphonia. For this, it was performed an intervention research, field, descriptive in nature. The population consisted of 60 subjects, divided into two groups, group therapy (GT, n = 35) and individual therapy (IT, n = 25), seeking speech therapy in Clinical School Voice Therapy at UFPB in the city of João Pessoa - PB. We used the URICA-Voice protocol to assess the patient's pre and post stage of readiness voice therapy. For data analysis, we used statistical analysis descriptive and inferential such as the Student's T test, and tests to verify the association between the variable compromise with age, sex, education and laringeal report. How characterization of the research, most, 71.7% (n = 43) were female; with respect to education, in GT 31.4% were in elementary school incomplete, while in IT 40% completed high school; laringeal report both groups showed a higher percentage in the injury category in the membranous portion the vocal folds, with 42.9% and 68% in GT IT; on the stage of readiness, the two groups had a higher percentage in the contemplation stage, with 80% and 71.4% in GT; and 84% and 72% in IT, in pre and post moments respectively. The results revealed no statistical difference among the groups. Only in the association between post-therapy gain with education in individual therapy group showed significant (P = 0.035) in all other variables showed no significance.